Long-term stability of dental adhesive incorporated by boron nitride nanotubes. Issue 3 (March 2018) - Degrazia, Felipe Weidenbach; Leitune, Vicente Castelo Branco; Visioli, Fernanda; Samuel, Susana Maria Werner; Collares, Fabrício Mezzomo
Highlights: BNNT incorporation up to 0.1% stabilized microtensile bond strength after 6 months. All BNNT's groups showed higher microtensile bond strength than 0% after 6 months. Degree of conversion and polymerization rate increased after incorporating BNNT. No cytotoxicity was found after incorporation of adhesive with BNNT. Abstract: Objective: The aim of this study was to evaluate physicochemical properties, long-term microtensile bond strength and cytotoxicity of methacrylate-based adhesive containing boron nitride nanotubes (BNNTs) as fillers. Methods: A dental adhesive was formulated using BisGMA/HEMA, 66/33 wt% (control). Inorganic BNNT fillers were incorporated into the adhesive at different concentrations (0.05, 0.075, 0.1 and 0.15 wt%). Analyses of degree of conversion (DC), polymerization rate [Rp.(s −1 )], contact angle (CA) on dentin, after 24 h and 6 months microtensile bond strength (μTBS-24 h and 6 months) were assessed. Cytotoxicity was performed through viability of fibroblast cells (%) by sulforhodamine B (SRB) colorimetry. Results: DC and max. polymerization rate increased (p < 0.05) after incorporating 0.075 and 0.1 wt% BNNT. The contact angle on dentin increased (p < 0.05) after incorporating 0.15 wt% BNNT. The μTBS-24 h showed no changes (p > 0.05) after incorporating up to 0.15 wt% BNNT comparing to control. After 6 months, μTBS decreased (p < 0.05) for control and 0.15 wt% BNNT and BNNT groups up to 0.15 wt% showed higher μTBS than control (p < 0.05). No difference of fibroblast growth was found among adhesives (p > 0.05) and up to 19% of cell viability was found comparing 0.05 wt% BNNT to positive control group (100%). Significance: Incorporating boron nitride nanotubes up to 0.1 wt% into dental adhesive increased the long-term stability to dentin without decreasing viability of fibroblast cell growth. Thus, the use of BNNTs as filler may decrease failure rate of current dentinal adhesives.